SBU's Bolivar Campus Set to Graduate First PLBSN Cohort on May 14 - Office of Marketing & Communications (Southwest Baptist University, 2021)
Two and a half years after classes began for the Pre-Licensure Bachelor of Science in Nursing (PLBSN) program on Southwest Baptist University’s Bolivar campus, the first cohort will graduate on Friday, May 14.